Epistemologi Ukhuwah sebagai Falsafah Pemikiran Islam - Matroni (Fahima, 2022)
In the scientific system, a comprehensive critical epistemology paradigm for Muslims is needed to explore the spirit of critical epistemology. This is important because Indonesia is a dynamic country, thus requiring a dynamic epistemological foundation. Based on this description, this study aims to examine the epistemological paradigm of ukhuwah as well as the philosophy of critical epistemology it builds. The theoretical framework of this research is the epistemology of Muhammad Abit Aljabiri, while the research method used is descriptive-analytical. The results of this study indicate that the ukhuwah epistemology paradigm is part of critical epistemology, so that the scientific products give birth to the critical epistemology needed by society and the nation. The critical epistemology paradigm is known as the contemporary paradigm because of the effort to combine ukhuwah Islamiyah, ukhuwah basyariyah and ukhuwah wathaniyah. The ukhuwah product emphasizes that the three ukhuwahs are a critical epistemology capable of maintaining and maintaining Pancasila and NKRI, which are a manifestation of Islamic values - an individual responsibility as well as a collective obligation because they fall under the category of academically recognized Islamic scholarship. known as critical epistemology.